교사가 지각한 유아기 외현화 문제행동의 발달 경로 - 잠재성장곡선모형을 적용한 단기종단연구 - 강지현; 오경자; Kang, Ji-Hyeon; Oh, Kyung-Ja (Korean Journal of child studies, 2009)
The purpose of this study was to identify developmental trajectories of externalizing problems in preschoolers and to investigate dimensions of temperament and parental behaviors associated with trajectory groups. Subjects were 180 3- to 5-year-old preschoolers (96 males, 84 females) in the metropolitan area of Seoul. They were assessed three times at 5 month intervals over a one year period. Teachers reported on children's behavior problems, and parents reported on children's temperaments. Latent Growth Curve Modeling Analysis with cohort sequential design revealed externalizing behaviors gradually decreased between 3 and 6. At the 6-year-old level externalizing behaviors were associated with high novelty seeking temperament. The results were discussed in terms of the importance of longitudinal research in developmental psychopathology.